PREVENTIVE PRINCIPLES OF DISEASES ACCORDING TO AYURVEDA - Raju, *Mahesh; Yalgachin, Gurubasavaraj; Bhavani, Durga (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda the most ancient science of life, practiced in India for thousands of years based on its own unique fundamental principles such as prevention of disease, maintenance of health and promotion of longevity of life. Ayurvedic classics give special emphasis on preventive aspects like practising Dinacarya, Nishacharya, Rithucharya, Nithya sevaniya ahara, Varjana of Nidhana sevan and Pragnaparadha, undergoing regular Rithu shodhana etc., these are the important points which have been considered as the most conducive factors for maintenance of life and health. Trayopasthamba consists of Ahara (food), Nidra (Sleep) and Brahmacarya (Good conduct). Each Upasthamba has its own importance in prevention of disease. Ahara (diet) has been considered as the first one which shows its prime importance. Intake of wholesome and unwholesome diet is responsible for prevention and production of various diseases respectively including life style disorders. Acharya Charaka has clearly stated, that a daily diet should be (of such quality), which not only helps to maintain present well-being but serves as a prophylactic against coming diseases. This is a very important aspect of preventive medicine as mentioned in Ayurveda classics. Lifestyle disorders are a big problem for our society today. Such diseases mainly result from life style related factors such as unhealthy diet and dietary habits, lack of physical activity and lack of awareness regarding the preventive aspects of diseases etc. In this article, we are mainly concerned with the various principles of prevention of diseases and maintenance of healthy life is discussed as mentioned in the Ayurveda.